Optimalisasi Asuhan Keperawatan Untuk Meningkatkan Konsep Diri Pada Pasien Skizofrenia Dengan Harga Diri Rendah Kronis - Dewi Oktoviani; Erida Fadila; Evi Nurmala Fia; Kiki Ameliya; Rizal Nova Jalaludin (Awatara Publisher, 2024)
High-quality nursing care is key to improving the overall quality of health services and the image of healthcare institutions in the eyes of the public. This study highlights the importance of continuous assessment and improvement of nursing practice on professional standards. The research methodology employed was descriptive qualitative, focusing on holistic nursing care for patients with Paranoid Schizophrenia at Room Lily 12 of RS Soerojo. Through comprehensive observation and interviews with patients, families, and the healthcare team, along with medical record analysis, this study explores the patients' experiences in various aspects of social interaction and responses to interventions, aiming to develop individualized and holistic care strategies. Therapeutic approaches utilized include Cognitive Behavioral Therapy (CBT), psychoeducation, and schizophrenia counseling. Nurses play an active role in the formulation of a comprehensive care plan that includes medication, cognitive behavioral therapy, and family support, which has been shown to strengthen self-concept. Collaboration with psychiatrists and other health professionals adds a medicinal and holistic dimension to the care plan.